Penatalaksanaan Fisioterapi Pada Pasca Pemasangan Open Reduction Internal Fixation (Orif) Fraktur 1/3 Medial Humeri Sinistra Di Rst. Dr. Soedjono Magelang - Wandira, Salwa, Arif Pristianto, SSt.FT.,M.Fis (2017)
The 1/3 medial fracture of the left humis is a fracture that occurs in the left part of the humeral bone located in the third part of the bone. Fractures are a painful trauma, limited range of motion of the joints, and oedem in the upper left arm. Physiotherapy in this case can decrease pain, increase joint motion, and reduce oedem with IRR modalities, Exercise Therapy, and Shoulder Wheel Exercise. After 6 weeks of treatment the result of the decrease of silent pain was T0: 6,3 to T6: 4,7, T0: 0 to T6: 0, T0: 8 to T6: 7,2. The increased scope of joint motion of the horizontal plane of T0: 00 - 00 - 1100 becomes T6: 30 - 00 - 1300, frontal plane T0: 200 - 00 - 900 becomes T6: 400 - 00 - 1100. The reduction of the left axilla axilla is T0: 46.5 to T6: 42.5 cm, medial humeral T0: 39 cm to T6: 35 cm, distal humeral T0: 35 cm to T6: 32.5 cm. Infra red can reduce pain and oedem, while exercise therapy and shoulder wheel exercise can increase the scope of motion of the joints.